Planar inorganic five-membered heterocycles with σ + π dual aromaticity in both S0 and T1 states. Issue 36 (8th September 2022) - Gu, Xiaojiao; Yang, Le; Jin, Peng
Abstract : Density functional theory calculations reveal that several planar inorganic five-membered rings may have unprecedented adaptive σ + π dual aromaticity. Abstract : Cyclic species being aromatic in both the lowest singlet and triplet electronic states (so-called adaptive aromaticity) are scarce. To date, the reported systems have been mostly organometallic heterocycles with the aromaticities in the two states having the same origin of either σ- or π-electron delocalization ( i.e., adaptive σ or π aromaticity). Herein, an exhaustive density functional theory study was conducted for 90 planar inorganic five-membered heterocycles in the forms of XY4 and XY2 Z2 (X = O or S; Y and Z = N, P, As, Sb or Bi). They all contain 6π electrons and thus should be aromatic and antiaromatic in the lowest singlet and triplet states, respectively, according to classical Hückel's 4 n + 2 and Baird's 4 n π-electron rules. To our surprise, however, several of them ( e.g., ON2 As2, ON2 Bi2 and SAs2 Sb2 ) exhibit considerable aromatic characters in both S0 and T1 states, as confirmed by multiple aromaticity indices. More interestingly, further analyses reveal that their aromaticities in the two states may unprecedentedly stem from both σ- and π-electron delocalization. Thus, they likely bear unusual adaptive σ + π dual aromaticity. By finding adaptive aromatics in rather simple inorganic unsaturated systems, our work extends this emerging aromaticity concept to the big inorganic world.